A Simple Photovoltaic Experiment for Measuring Planck’s Constant Using Colour Lasers - Nuri Nuri; Putut Marwoto; Sunyoto Eko Nugroho; Agus Yulianto; Bambang Subali; Sulhadi Sulhadi; Sumarli Sumarli (Variabel, 2025)
The photovoltaic experiment provided a simple, affordable method to determine Planck’s constant through empirical learning. This experiment allowed students to present concrete data using easily available, low-cost materials. The experiment utilised a photovoltaic method, employing a simple, self-designed setup that used three laser pointers with wavelengths of 650nm (red), 535nm (green), and 405nm (blue) as independent variables. A 6V, 1W mini solar cell was used as the target, while the speed of light and electron charge were treated as control variables. The laser pointers were powered by a 3V battery. The data were analysed by plotting the relationship between 1/λ (inverse wavelength) and the measured voltage as the dependent variable. A linear regression analysis was performed to obtain the gradient, which was used to calculate Planck’s constant. The experiment yielded a calculated Planck’s constant of 7.09×10-35Js, with a deviation of 5.69 x 10-34Js, resulting in a relative error of 8.89%. This relative error could be attributed to several factors, including refraction effects caused by the glass layer and adhesive used to protect the semiconductor plate of the solar cell, as well as discrepancies between the actual wavelengths of the laser beams and the labelled wavelengths on the laser pointers.